Is there a trade-off between maximum jumping and throwing capability in the handball jump throw? - McGhie, D.; Sandbakk, O.; Østerås, S.; Ettema, G. (SAGE open, 2019)
This study examined the potential trade-off in performance between maximum physical capabilities in the handball jump throw, a fundamental skill comprised of two mechanically independent tasks. Elite handball players performed jump throw actions from a force plate for each of three instructions: jump at maximum capability, throw at maximum capability, and jump and throw at maximum capability simultaneously. Jump height and throwing velocity were derived from motion capture data. When jumping and throwing at maximum capability simultaneously, no trade-off between jump height and throwing velocity was present, but rather a concurrent decline from their respective maximums. This decline could be explained by mechanical factors related to movement execution; magnitudes of directional impulses favored vertical movement for jumping and horizontal movement for throwing. However, no explanation for differences in total magnitude of impulse between instructions was evident. Due to the expertise of the participants, information processing should not be a limiting factor, leaving movement strategy as the most likely explanation for the present findings.